Matharpacady-04.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Lawrence D'Souza, an East Indian, is undertaking renovations at 11 Matharpacady. The East Indians have lived at Matharpacady for more than two centuries. The East Indians—as recorded in history—are the original inhabitants living in the seven islands of Bombay, Salsette, and Bassein (Vasai). Belonging to various native communities, they were converted to Catholicism by missionaries in the 16th and 17th centuries, when Bombay was governed by the Portuguese.